Lignocellulosic Ethanol Biorefinery: Valorization of Lignin-Rich Stream through Hydrothermal Liquefaction - Edoardo Miliotti (Energies, 2019)
Hydrothermal liquefaction of lignin-rich stream from lignocellulosic ethanol production at an industrial scale was carried out in a custom-made batch test bench. Light and heavy fractions of the HTL biocrude were collected following an ad-hoc developed two-steps solvent extraction method. A full factorial design of experiment was performed, investigating the influence of temperature, time and biomass-to-water mass ratio (B/W) on product yields, biocrude elemental composition, molecular weight and carbon balance. Total biocrude yields ranged from 39.8% to 65.7% w/w. The Temperature was the main influencing parameter as regards the distribution between the light and heavy fractions of the produced biocrude: the highest amount of heavy biocrude was recovered at 300 °C, while at 350 and 370 °C the yield of the light fraction increased, reaching 41.7% w/w at 370 °C. Instead, the B/W ratio did not have a significant effect on light and heavy biocrude yields. Feedstock carbon content was mainly recovered in the biocrude (up to 77.6% w/w). The distribution between the light and heavy fractions followed the same trend as the yields. The typical aromatic structure of the lignin-rich stream was also observed in the biocrudes, indicating that mainly hydrolysis depolymerization occurred. The weight-average molecular weight of the total biocrude was strictly related to the process temperature, decreasing from 1146 at 300 °C to 565 g mol−1 at 370 °C.